Temporal dynamics and drivers of landscape‐level spread by emerald ash borer. Issue 6 (15th April 2020) - Ward, Samuel F.; Fei, Songlin; Liebhold, Andrew M.
Abstract: Non‐native insects pose threats to forest health and often spread via stratified dispersal in which long‐distance jumps cause elevated rates of range expansion. Quantifying patterns and developing models of spread are central to understanding drivers of invasion and forecasting future invasions. We investigated the utility of models for characterizing and predicting spread of emerald ash borer (EAB), quantified temporal dynamics of spread and identified correlates of county‐level invasion risk. We estimated rates and frequency of EAB spread and length of long‐distance jumps throughout the contiguous USA from 1997 to 2018 and compared observed patterns with model predictions. A time‐to‐event model was then developed at the county level to assess the influence of habitat characteristics and propagule pressure on invasion risk. The final model was used to forecast invasion risk across the contiguous USA. Range expansion by EAB accorded well with model predictions. Following the initial establishment phase, range expansion rates were biphasic, shifting to a faster, linear pattern around 2002 and then declining from 2015 onwards. From 2003 onwards, EAB invaded 6–134 new counties per year, including a mean of 14 discrete jumps per year averaging 93 ± 7 SE km. Risk of spread was positively associated with proximity to previously invaded areas, human population density and densities of ash and non‐ash trees in rural forests but negatively associated with temperature. Synthesis and applications . At the regional level, the invasion by emerald ash borer appears to be entering the saturation phase, indicating that most high‐risk counties in the eastern USA have been invaded. Even though spread has recently slowed, counties in close proximity to invaded areas and that have high densities of humans and trees are at the greatest risk of becoming invaded. Taken together, our findings provide insight into historical and future dynamics of range expansion by emerald ash borer, which can be used to guide risk assessments for potential invaders capable of frequent long‐distance dispersal. Abstract : At the regional level, the invasion by emerald ash borer appears to be entering the saturation phase, indicating that most high‐risk counties in the eastern USA have been invaded. Even though spread has recently slowed, counties in close proximity to invaded areas and that have high densities of humans and trees are at the greatest risk of becoming invaded. Taken together, our findings provide insight into historical and future dynamics of range expansion by emerald ash borer, which can be used to guide risk assessments for potential invaders capable of frequent long‐distance dispersal.